Pengaruh pemberian Iodine-131 terhadap viabilitas cell line Triple Negative Breast Cancer (TNBC) - Monika, Katrin; Elliyanti, Aisyah; Kurniawati, Yulia (Faculty of Medicine, Universitas Andalas, 2023)
AbstractObjective: To determine the effect of Iodine-131 administration on the viability of triple negative breast cancer cell lines and the IC50 value of Iodine-131. Methods: This study was a true experimental study using the MTT assay method to measure cell line viability after being given Iodine-131 at a dose of 7.8; 15.6; 31.3; 62.5; 125; 250; and 500 µCi for 24 hours. The research sample was the MDA-MB231 cell line which represents the Triple Negative Breast Cancer (TNBC) subtype of breast cancer. The IC50 value of Iodine-131 cell line MDA-MB231 was calculated using the GraphPad Prism-9 software. The results were analyzed using the Kruskal-Wallis and Post-Hoc Kruskal-Wallis tests, if p <0.05 was considered to significantly affect cell viability. Results: Iodine-131 affected cell viability in the MDA-MB231 cell line with a p<0.05. The IC50 value of Iodine-131 on the MDA-MB231 cell line was 255.7 µCi. Conclusion: Administration of Iodine-131 at a dose of 500 µCi for 24 hours significantly reduced the viability of the MDA-MB231 cell line. Iodine-131 dose of 255.7 µCi can inhibit 50% viability of the MDA-MB231 cell line.Keywords: Iodine-131; cell viability; cell line MDA-MB231; TNBC; IC50